Effectiveness of Coaching and Mentoring on Employee Quota Attainment at Bpo Company in Cubao Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Organizations must recognize that they face real problems and prioritize them in order topreserve their human resources. Managers should pay special attention to all HR functionsthat play an important role in various organizations. This is especially important in coachingand mentoring conversations to help employees meet their quotas.Quality work: As stated in the questionnaire survey, strategies for mentoring and coaching interms of Quality work are effective in the employees' workplace. It helps the employees toproduce quality work, avoiding distraction and digression, ranked by employees to the top toa very great extent. Mentor Training: set clear expectations and goals at the beginning of therelationship strategy that is effective for coaching and mentoring, resulting in the employeesurvey questionnaire.The researchers recommend that the company should have a celebration of theaccomplishments at the end of the week for productivity and their recognition of the effort ofthe employee as the result of the salary increase. Make a goals road map as a plan andschedule for the training of the employees to be effectively evaluated for them to makequality work.
Keywords: Business Administration